High-quality RNA isolation from pigment-rich Dendrobium flowers - Khairul Anuar, Muhammad Asyraf; Mazumdar, Purabi; Lau, Su Ee; Tan, Tian Tian; Harikrishna, Jennifer Ann (Springer Verlag (Germany), 2019)
Isolation of high-quality RNA from Dendrobium flowers is challenging because of the high levels of pigment, polysaccharides, and polyphenols. In the present study, an efficient CTAB method for RNA extraction from the pigment-rich flowers of Dendrobium was optimised. The optimised method yielded high quantities of RNA (10.1–12.9 µg/g). Spectrophotometric values of A260/280 in the range of 2.2 to 2.4 and A260/230 values of 2.0 suggested that the isolated RNA was free of polyphenols, polysaccharides, and protein contaminants. RNA integrity numbers determined by microfluidics were in the range of 7.9–8.9 indicative of intact RNA. In the improved method, the addition of 3 M NaCl and 3% PVP-10 in the extraction buffer, followed by an incubation period of 45 min at 65 °C, eliminated most of the polysaccharides, polyphenolic compounds, and denatured protein. Extraction with phenol:chloroform:isoamyl alcohol (125:24:1) effectively removed pigments from the aqueous phase, while the precipitation of RNA with lithium chloride minimised the co-precipitation of protein, DNA, and polysaccharide and resulted in the extraction of high quality of RNA. The suitability of the RNA for downstream processing was confirmed via RT-PCR amplification of Chalcone synthase gene from cDNA prepared from RNA isolated from different developmental stages of the flower of a Dendrobium hybrid. The present method will be highly useful for the isolation of RNA from pigment, polyphenol, and polysaccharide-rich plant tissues. © 2019, King Abdulaziz City for Science and Technology.